1999
DOI: 10.1038/sj.ejcn.1600714
|View full text |Cite
|
Sign up to set email alerts
|

The effect of magnesium supplementation on biochemical markers of bone metabolism or blood pressure in healthy young adult females

Abstract: Objectives: To investigate the effects of increasing Mg intakes, above the usual dietary intake, on blood pressure and on biomarkers of bone metabolism in healthy young adult females. Design: A double-blind, placebo-controlled, randomised crossover Mg intervention trial. Setting: The study was conducted in the Department of Nutrition, University College, Cork, Ireland. Subjects: Twenty-six healthy (normotensive) adult females aged 20 ± 28 y were recruited from University College, Cork. Intervention: Subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 42 publications
3
21
2
Order By: Relevance
“…The latter is consistent with Mg supplementation studies that have shown no change in serum Mg despite increased dietary intakes (Dimai et al, 1998;Doyle et al, 1999). An increase in Mg bioavailability might have been detected from measurements of intracellular Mg. Large Mg supplements (250 mg=day for 4 weeks) produce modest PTH and bone resorption effects of milk JH Green et al increases in erythrocyte Mg concentration (Doyle et al, 1999). However, a daily supplement of an amount of Mg that was similar to the one we used (125 mg=day), provided as Mg citrate malate for 3 weeks has been shown to have no impact on intracellular erythrocyte concentration (Basso et al, 2000).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The latter is consistent with Mg supplementation studies that have shown no change in serum Mg despite increased dietary intakes (Dimai et al, 1998;Doyle et al, 1999). An increase in Mg bioavailability might have been detected from measurements of intracellular Mg. Large Mg supplements (250 mg=day for 4 weeks) produce modest PTH and bone resorption effects of milk JH Green et al increases in erythrocyte Mg concentration (Doyle et al, 1999). However, a daily supplement of an amount of Mg that was similar to the one we used (125 mg=day), provided as Mg citrate malate for 3 weeks has been shown to have no impact on intracellular erythrocyte concentration (Basso et al, 2000).…”
Section: Discussionsupporting
confidence: 87%
“…Serum PTH and biochemical markers of bone turnover have been shown to be transiently reduced during the first 5 -10 days of 30 days of Mg supplementation in young men (Dimai et al, 1998). However, Mg supplementation for longer than 2 weeks does not lead to significant changes in bone resorption markers or serum PTH (Dimai et al, 1998;Doyle et al, 1999;Basso et al, 2000). We have previously observed decreases in bone resorption in response to 4 weeks of supplementary Mg-enriched high Ca milk that were greater than those seen for high Ca milk without additional Mg (Green et al, 2000), but that study did not include any measurements of serum PTH, Ca or Mg.…”
Section: Introductionmentioning
confidence: 99%
“…Our results also extended the finding of previous work which demonstrated that magnesium was a significant predictor of rate of change of total body BMD among premenopausal women [36]. Although the beneficial effect of magnesium on bone health was shown in observational studies, experimental studies examining the effects of magnesium supplementation on bone health were smallscaled, with conflicting results [37,38]. More studies are needed to confirm the association of magnesium with bone health post stroke.…”
Section: Magnesium Intake and Bone Healthsupporting
confidence: 88%
“…Of the 22 studies in this meta-analysis, 13 reported adverse effects from the intervention and placebo treatments, 4,15,16,18 --22,28 --32 six reported no adverse effects 24,33 --38 and three did not report any information relating to adverse effects. 17,23,25 Of these studies, the adverse effects were largely either diarrhoea, or unspecific mild abdominal or bone pain. Only three studies reported serious adverse effects from the treatments that led to withdrawal from the investigations: Lind et al 29 reported one case of visual impairment of a subject on magnesium treatment; Wirrel et al 31 reported a myocardial infarction of a subject but did not specify the treatment that the subject was receiving; Plum-Wirrell et al 32 reported a blood coagulation defect of one subject but also did not specify the treatment arm.…”
Section: Discussionmentioning
confidence: 99%